2005
DOI: 10.1186/1471-2148-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Diverse spatial, temporal, and sexual expression of recently duplicated androgen-binding protein genes in Mus musculus

Abstract: Background: The genes for salivary androgen-binding protein (ABP) subunits have been evolving rapidly in ancestors of the house mouse Mus musculus, as evidenced both by recent and extensive gene duplication and by high ratios of nonsynonymous to synonymous nucleotide substitution rates. This makes ABP an appropriate model system with which to investigate how recent adaptive evolution of paralogous genes results in functional innovation (neofunctionalization).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 48 publications
1
33
1
Order By: Relevance
“…Furthermore, steroids released into mouse saliva and tears can be bound by androgen-binding proteins (ABPs) (96). ABPs are secretoglobins that form heterodimeric complexes with steroids bound at the dimer interface (96).…”
Section: Chemical Diversity Of Mammalian Pheromonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, steroids released into mouse saliva and tears can be bound by androgen-binding proteins (ABPs) (96). ABPs are secretoglobins that form heterodimeric complexes with steroids bound at the dimer interface (96).…”
Section: Chemical Diversity Of Mammalian Pheromonesmentioning
confidence: 99%
“…ABPs are secretoglobins that form heterodimeric complexes with steroids bound at the dimer interface (96). The steroid-binding capacity of ABPs is reminiscent of the pheromone-binding properties of lipocalins (see below).…”
Section: Chemical Diversity Of Mammalian Pheromonesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the absence of typical intraspecific social behavior in male GTG-obese mice was associated with the total or partial failure to release a factor or factors from the submaxillary glands. Androgen binding proteins which are secreted by the mouse submaxillary gland and found in saliva, were shown to be involved in some behavioral responses such as mate selection [8, 39] and shown not to be secreted in urine [41]. Kimoto et al, [27] found that extract from submaxillary gland induced robust expression of c-fos in female VSNs.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Laukaitis et al, [8] observed the expression of many androgen binding proteins (Abps) in various glands in the head and neck including the lacrimal and salivary glands. Salivary Abp mediates mate preference [8] and saliva is involved in sexual communication [9] indicating the presence of pheromones in the glands involved in saliva production. Currently, no data are available on the presence of volatile pheromones in saliva as has been shown for urine [10].…”
Section: 0 Introductionmentioning
confidence: 99%